The soil micro-fungi of selected areas of Malaysia - Paul A. Volz; Ahmad J. Makhtar (Universiti Kebangsaan Malaysia, 1997)

(untitled)
Four areas of Malaysia were selected for the study of filamentous micro fungi occupying soil habitats. Ampang, Kota Bharu, Bandar Melaka, and Kuantan were examined for micro-fungi species content and diversity of isolates. Species recovered from the soils of Malaysia, represent 63 genera and four classes, according to current concepts of fungal taxonomy (Clements and Shear, 1964; Domsch and Gams, 1980). Most isolates belonged to the imperfect fungal class Deuteromycetes, a few species represented the Zygomycetes, and only isolated incidents of Mastigomycetes and Ascomycetes were found occupying the soil of these regions.